PENGEMBANGAN TRANSMISI DAYA DENGAN CAHAYA LASER UNTUK SUPLAI DAYA JARAK JAUH PADA SENSOR TILT METER - Rodhiah, Salsa Ariani; Harmadi; Widiyatmoko, Bambang (Jurnal Fisika Unand, 2025)
This study aimed to develop and test a Power over Fiber (PoF) system as a remote power supply to support the operation of a tilt meter sensor. The sensor is used to detect changes in ground inclination, which serves as an early indicator of landslide potential in disaster prone areas. The tests were conducted using infrared laser diodes with wavelengths of 808 nm and 940 nm as the optical power source. Light from the laser diode was transmitted through multimode optical fiber to the AFBR-POC206L photovoltaic device, which has the ability to convert optical power into electrical power. The test results showed that the photovoltaic device was capable of generating sufficient electrical power to support the operation of the tilt meter sensor and charge lithium polymer batteries. The PoF system successfully provided a stable power supply to operate the tilt meter sensor, demonstrating its ability to meet the power needs of geotechnical devices. This study proves that the PoF system can serve as a reliable and efficient alternative for remote power supply, particularly in geotechnical monitoring applications. Based on the results obtained, the PoF system shows great potential for implementation in various environmental monitoring applications requiring remote power supply.